Acceleration of Functional Maturation and Differentiation of Neonatal Porcine Islet Cell Monolayers Shortly In Vitro Cocultured with Microencapsulated Sertoli Cells. (18th October 2009) - Mancuso, Francesca; Calvitti, Mario; Luca, Giovanni; Nastruzzi, Claudio; Baroni, Tiziano; Mazzitelli, Stefania; Becchetti, Ennio; Arato, Iva; Boselli, Carlo; Ngo Nselel, Monique D.; Calafiore, Riccardo
Abstract : The limited availability of cadaveric human donor pancreata as well as the incomplete success of the Edmonton protocol for human islet allografts fasten search for new sources of insulin the producing cells for substitution cell therapy of insulin-dependent diabetes mellitus (T1DM). Starting from isolated neonatal porcine pancreatic islets (NPIs), we have obtained cell monolayers that were exposed to microencapsulated monolayered Sertoli cells (ESCs) for different time periods (7, 14, 21 days). To assess the development of the cocultured cell monolayers, we have studied either endocrine cell phenotype differentiation markers or c-kit, a hematopoietic stem cell marker, has recently been involved with growth and differentiation ofβ -cell subpopulations in human as well as rodent animal models. ESC which were found to either accelerate maturation and differentiation of the NPIsβ -cell phenotype or identify an islet cell subpopulation that was marked positively for c-kit. The insulin/c-kit positive cells might represent a new, still unknown functionally immatureβ -cell like element in the porcine pancreas. Acceleration of maturation and differentiation of our NPI cell monolayers might generate a potential new opportunity to develop insulin-producing cells that may suite experimental trials for cell therapy of T1DM.